2011
DOI: 10.1007/s10658-011-9897-9
|View full text |Cite
|
Sign up to set email alerts
|

β-aminobutyric acid protects Brassica napus plants from infection by Leptosphaeria maculans. Resistance induction or a direct antifungal effect?

Abstract: Resistance to infection in plants can be induced by treatment with various chemicals. One such compound is β-aminobutyric acid (BABA). Its positive effect on disease resistance has been noted in several pathosystems. Here we demonstrate that treatment with BABA protects Brassica napus plants from infection by the fungal pathogen Leptosphaeria maculans. Surprisingly, BABA also displayes in vitro antifungal activity against L. maculans with EC 50 similar to the fungicide tebuconazole. Both spore germination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 40 publications
(53 reference statements)
0
23
1
Order By: Relevance
“…Recently, however, Šašek et al (2012) found BABA had direct antifungal activity against Leptosphaeria maculans and the effect was comparable with the fungicide tebuconazole [30]. Our study showed that both BABA and GABA had direct toxicity to S. avenae when added to artificial diet.…”
Section: Discussioncontrasting
confidence: 44%
“…Recently, however, Šašek et al (2012) found BABA had direct antifungal activity against Leptosphaeria maculans and the effect was comparable with the fungicide tebuconazole [30]. Our study showed that both BABA and GABA had direct toxicity to S. avenae when added to artificial diet.…”
Section: Discussioncontrasting
confidence: 44%
“…This could be attributed to a lower sporulation rate of the pathogen. BABA has a direct toxic effect on some pathogens such as Leptosphaeria maculans [89], but not towards P. infestans [66]. Tobacco, tomato, and pepper plants express SAR signals and induce PR1a, chitinase and glucanase expression after BABA application [52,54].…”
Section: Plant Resistance Inducers (Pris) In Solanaceae Speciesmentioning
confidence: 99%
“…One of the most economically important diseases of Brassica, especially oilseed rape, is Blackleg disease or Phoma stem canker, which is induced by the L. maculans species complex (Howlett et al, 2001;Humpherson-Jones, 1985;Šašek et al, 2011). The disease is present worldwide, being more severe in countries with high summer temperatures.…”
Section: Economically Important Pests and Pathogens Of Brassica Speciesmentioning
confidence: 99%